2008
DOI: 10.1093/schbul/sbn146
|View full text |Cite
|
Sign up to set email alerts
|

Dyskinesia and Parkinsonism in Antipsychotic-Naive Patients With Schizophrenia, First-Degree Relatives and Healthy Controls: A Meta-analysis

Abstract: The results suggest that movement disorders, and by inference abnormalities in the nigrostriatal pathway, are not only associated with schizophrenia itself but may also be related to the (genetic) risk of developing the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
2
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 63 publications
7
89
2
5
Order By: Relevance
“…The present results linking pre-treatment EPS to symptom severity in first episode psychosis, to cognitive dysfunction, and to abnormalities of brain structure all support the proposal that similar observations in family members of patients with psychosis represent an endophenotype of the illness [5,6]. Findings concerning the course of extrapyramidal symptoms and the relationships to treatment response indicate the possible importance of thorough assessment for EPS at the entry into early psychosis treatment programs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The present results linking pre-treatment EPS to symptom severity in first episode psychosis, to cognitive dysfunction, and to abnormalities of brain structure all support the proposal that similar observations in family members of patients with psychosis represent an endophenotype of the illness [5,6]. Findings concerning the course of extrapyramidal symptoms and the relationships to treatment response indicate the possible importance of thorough assessment for EPS at the entry into early psychosis treatment programs.…”
Section: Discussionsupporting
confidence: 80%
“…Many of these same signs are described in family members of patients [5,6]. Most endophenotype studies investigate neurological soft signs, that appear to represent signs of developmental deviance [7,8].…”
mentioning
confidence: 94%
“…A recent meta-analysis calculated an odds ratio of 3.59 for spontaneous dyskinesia in schizophrenia [58]. However, a large negative study (n = 908) of Southeast Asian drug-naïve, first-episode schizophrenia subjects was not included in the meta-analysis [59].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…The Caligiuri group [73,74] used a variety of instrumental measures to reappraise spontaneous parkinsonism in schizophrenia, a finding that has later been replicated using clinical rating scales [13,34,35,75,76]. Meta-analytic results demonstrated an odds ratio of 5.32 for spontaneous parkinsonism in never-treated schizophrenia subjects [58]. Parkinsonism of unmedicated first-episode patients was shown to deteriorate with antipsychotic treatment in some patients (28%), while in others, parkinsonism was unchanged (15%) or ameliorated (6%) with treatment [57].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…16,17 Interestingly, several studies have shown that spontaneous movement disorders, mainly spontaneous dyskinesia, may be present in antipsychotic-naive schizophrenia patients and may represent an intrinsic neuromotor component of this disorder. [18][19][20] If this concept is valid, it is not possible to differentiate between dyskinesia related to the illness of schizophrenia and drug-induced TD.…”
Section: Introductionmentioning
confidence: 99%